The determination and pollution analysis of β-N- methylamino-L-alanine and its isomers in algal health products - WANG Chen; YUAN Guanxiang; LUO Qing; QIN Xiaoyun; YANG Shengyuan; LIU Guihua (Zhongguo shipin weisheng zazhi)
ObjectiveTo investigate the pollution levels of algal health products in China， the liquid chromatography-mass spectrometry method based on AQC derivation for BMAA and its isomers in algal health products was established.MethodsThe samples were treated by acid hydrolysis， nitrogen concentration and AQC derivatization， and then analyzed by ultra-performance liquid chromatography-tandem mass spectrometry， quantified by internal standard methods of two commercial isotope standards.ResultsIn the linear range of 0.25-100 μg/L， the correlation coefficients of BMAA toxins were all above 0.998. When the samples were 15 mg and the volume were 20.0 mL， the detection limits of BMAA， AEG and DAB were 133， 133 and 200 μg/kg， respectively. And the quantitative limits were 443， 443 and 667 μg/kg， respectively. The recoveries were between 86.7% and 126.0%， with the relative standard deviations between 1.1% and 14.0%. The detection rate for DAB was the highest in all samples （86%）， followed by AEG （23%） and BMAA （14%）. The concentrations of DAB， AEG and BMAA in the detectable samples were between 385-2 305， 250-518 and 472-698 μg/kg， respectively.ConclusionThe established method based on AQC derivation LC-MS/MS method is more efficient and accurate. The levels of BMAA toxins in domestic algae health products were relatively high， it should be paid more attention and to strengthen the supervision.